Intelligent System Modeling for Aid Mapping and Distribution with Genetic Algorithm (Elkom: Jurnal Elektronika dan Komputer, 2025)
Efficient aid distribution is a major challenge in the distribution process. This study aims to design an intelligent system capable of mapping and distributing aid optimally with an algorithmic approach. The methodology used includes system modeling using the Unified Modeling Language (UML), the design of a relational database structure, and the design of a distribution algorithm based on priority criteria and logistics efficiency. UML is used to visually describe the system architecture, including use case, class, and activity diagrams. Database design is carried out to ensure data integrity and easy management of aid information, location, and recipient needs. The algorithm developed utilizes a heuristic approach to determine distribution routes and recipient priorities based on geographic location parameters. The results of this study are in the form of a prototype conceptual model that can used as a basis for developing a technology-based intelligent system to support an adaptive and responsive aid distribution process.